Commercial hydrogel product for drug delivery based on route of administration - Raeisi, Amin; Farjadian, Fatemeh (Frontiers in Chemistry, 2024)
Hydrogels are hydrophilic, three-dimensional, cross-linked polymers that absorb significant amounts of biological fluids or water. Hydrogels possess several favorable properties, including flexibility, stimulus-responsiveness, versatility, and structural composition. They can be categorized according to their sources, synthesis route, response to stimulus, and application. Controlling the cross-link density matrix and the hydrogels' attraction to water while they're swelling makes it easy to change their porous structure, which makes them ideal for drug delivery. Hydrogel in drug delivery can be achieved by various routes involving injectable, oral, buccal, vaginal, ocular, and transdermal administration routes. The hydrogel market is expected to grow from its 2019 valuation of USD 22.1 billion to USD 31.4 billion by 2027. Commercial hydrogels are helpful for various drug delivery applications, such as transdermal patches with controlled release characteristics, stimuli-responsive hydrogels for oral administration, and localized delivery via parenteral means. Here, we are mainly focused on the commercial hydrogel products used for drug delivery based on the described route of administration.